SARS-CoV-2 viral proteins trigger pain via TLR2/4-MyD88 pathway - Su, Wenliang; Wang, Xinrui; Gu, Minghui; Zheng, Qiwei; Yu, Jiawen; Mu, Dongliang (Frontiers in Molecular Neuroscience, 2025)
Somatosensory disorders, especially pain, are prominent symptoms of COVID-19. Except for the viral infection process, SARS-CoV-2 viral proteins might be directly sensed by corresponding receptors, thereby triggering nociceptive signals in the dorsal root ganglion (DRG) and spinal dorsal horn (SDH). Behavioral assays were performed to screen out the nociceptive effects of the SARS-CoV-2 envelope protein (S2E) and spike protein receptor binding domain (S2S-RBD). Further investigation revealed that the genetic knockdown of TLR2 in the DRG and SDH significantly alleviated pain induced by both S2E and S2S-RBD. In contrast, the knockdown of TLR4 did not mitigate S2E-related pain but did reduce S2S-RBD-associated pain. Additionally, the knockdown of MyD88 effectively alleviated both mechanical and thermal pain induced by S2E and S2S-RBD. These findings indicate that the TLR2/4-MyD88 axis mediates SARS-CoV-2 protein-induced pain, and the interaction between viral proteins and neuro-immune receptors might serve as a key pathogenic factor in COVID-19 somatosensory disorders, suggesting a promising therapeutic strategy for these symptoms.